Fish Species Identification Techniques: A Review - M. Hassoon, Israa (Al-Nahrain Journal of Science, 2022)
Fish species identification process is still problematical and time consuming, so automated fish identification is important. The performance of various fish identification techniques is compared depending on pre-processing, number of significant characteristics and identification correctness. The reason for writing this review stems from the importance of fish for humans as food and as a wealth which support the economy of countries. Therefore, it is necessary to shed light on fish and how to distinguish the beneficial and harmful ones, discover and identify fish diseases, and so on, which contributes in building a knowledge base available to all. The aim of this paper is present a review on various fish species identification techniques; pre-processing operations, features extraction methods, recognition/classification techniques and databases. This review will be helpful for beginner researchers, it can be used as a starting point for new fish species identification approaches.